Documenting Linguistic Knowledge in an Inuit Language Atlas - Murasugi, Kumiko; Ittusardjuat, Monica (Études Inuit Studies)

(untitled) (Centre interuniversitaire d’études et de recherches autochtones (CIÉRA), 2016)
The traditional method of orally transmitting language is weakening with the passing of fluent Elders and language erosion in contemporary Inuit society. Language documentation is a vital component of language maintenance and revitalization. In this paper we present a pilot online, multimedia cybercartographic Atlas of the Inuit Language in Canada, the goal of which is to help protect and strengthen the vitality of Inuit dialects through the documentation of their words. The main component of the atlas is a multidialectal database of written and spoken words. We discuss the role of dictionaries in language documentation, introduce the features of the atlas, explore the appeal of the atlas to different types of users (in particular, language learners), and present future directions for the atlas project.